Evaluation of the Efficacy and Safety of Ramelteon in Subjects with Chronic Insomnia - Zammit, Gary (American Academy of Sleep Medicine, 2007)
OBJECTIVE: To evaluate efficacy and safety of ramelteon (MT(1)/MT(2)-receptor agonist) in subjects with chronic primary insomnia. METHODS: Randomized, multicenter, double-blind, placebo-controlled trial of nightly ramelteon treatment (8 mg or 16 mg) in adults (N=405) with primary chronic insomnia (DSM-IV-TR). Latency to persistent sleep (LPS), TST, sleep efficiency, wake time after sleep onset, and number of awakenings were measured by polysomnography. Subject-reported measures were also assessed. RESULTS: LPS at Week 1 (primary measure) was significantly shorter with ramelteon 8 mg (32.2 min) or 16 mg (28.9 min) vs placebo (47.9 min; p <0.001). Significant improvements in LPS were maintained at Weeks 3 and 5. TST was significantly longer with both doses of ramelteon at Week 1 (p <0.001) vs placebo. Subject-reported sleep latency was significantly shorter with ramelteon 8 mg at Weeks 1, 3, and 5 (p <0.001) and ramelteon 16 mg at Weeks 1 and 3 (p ≤0.050) vs placebo. Wake time after sleep onset and number of awakenings were not significantly different with ramelteon 8 mg or 16 mg treatment vs placebo. Subjective TST was significantly longer with ramelteon 8 mg at Weeks 1, 3, and 5 (p ≤0.050) and ramelteon 16 mg at Week 1 (p = 0.003) vs placebo. Ramelteon had no clinically meaningful effect on sleep architecture, next-morning psychomotor tasks, alertness, or ability to concentrate. No withdrawal or rebound effects were observed. CONCLUSIONS: Ramelteon reduced LPS over 5 weeks of treatment in subjects with chronic insomnia, with no clinically meaningful sleep architecture alterations, next-morning residual pharmacologic effects, and no evidence of rebound insomnia or withdrawal. No numerical differences were observed between the 2 doses of ramelteon. CITATION: Zammit G; Erman M; Wang-Weigand S; Sainati S; Zhang J; Roth T. Evaluation of the efficacy and safety of ramelteon in subjects with chronic insomnia. J Clin Sleep Med 2007;3(5):495-504.